A new species of Pontoscolex earthworm (Rhinodrilidae, Clitellata) from the Gurupi Biological Reserve, along with records of earthworm species from the Amazon region of Maranhão, Brazil - Sousa, Sandriel Costa; Hernández-García, Luis Manuel; Rousseau, Guillaume Xavier (Zootaxa, 2020)
We describe a new species of the genus Pontoscolex from the Amazon region of Maranhão State in Brazil. The region is the most deforested and degraded in the biome, with only 25% of the original forest cover left. Pontoscolex awa sp. nov. has regular setae, very small spermathecae, and tubercula pubertatis band-shaped extending to AB line in XIX–XII. Common and genital setae are of similar length and without ornamentations; these features are new in the genus, although unknown in several species. The Gurupi Biological Reserve where the new species was found is the only integral protection area within the Belém Endemism Area and therefore of crucial importance for conservation of earthworms and other endemic organisms.